Synthesis of 1, 2-benzisoxazole tethered 1, 2, 3-triazoles that exhibit anticancer activity in acute myeloid leukemia cell lines by inhibiting histone deacetylases, and inducing p21 and tubulin acetylation. Issue 18 (15th September 2015) - Ashwini, Nanjundaswamy; Garg, Manoj; Mohan, Chakrabhavi Dhananjaya; Fuchs, Julian E.; Rangappa, Shobith; Anusha, Sebastian; Swaroop, Toreshettahally Ramesh; Rakesh, Kodagahalli S.; Kanojia, Deepika; Madan, Vikas; Bender, Andreas; Koeffler, H. Phillip; et al.
Graphical abstract: Highlights: We here describe the coupling of 1, 2, 3-triazoles to the third position of a 1, 2-benzisoxazole via CuAAC with various alkynes. PTB has been identified as the lead cytotoxic compound against the AML cell lines. An apoptotic effect of PTB was demonstrated using Annexin-V staining and flow cytometry analysis. In silico analysis suggested histone deacetylases as the mode-of-action of PTB. This has been experimentally validated by showing acetylation patterns in target proteins and examining expression of p21. Abstract: 1, 2, 3-Triazole-based heterocycles have previously been shown to possess significant anticancer activity in various tumor models. In the present study, we attached a 1, 2, 3-triazole moiety to the third position of a 1, 2-benzisoxazole heterocycle via copper(I)-catalyzed azide–alkyne cycloaddition (CuAAC) with various alkynes and established for the title compounds significant antiproliferative effect against human acute myeloid leukemia (AML) cells. Among the tested compounds, 3-(4-(4-phenoxyphenyl)-1 H -1, 2, 3-triazol-1-yl)benzo[ d ]isoxazole (PTB) was found to be the most potent antiproliferative agent with an IC50 of 2 μM against MV4-11 cells using MTT assay. Notably, PTB induced cytotoxicity in MOLM13, MOLM14 and MV4-11 cells with selectivity over normal bone marrow cells (C57BL/6). Furthermore, PTB was found to induce cytotoxicity by increasing apoptosis of AML cells (MOLM13, MOLM14 and MV4-11) as well as sub-G1 cell population and apoptotic cells at submicromolar concentrations, as shown by flow cytometry and Annexin-V staining, respectively. On the protein level we suggested histone deacetylases (HDACs) as the potential protein target of those compounds in silico, and the predicted target was next experimentally validated by measuring the variations in the levels of p21, cyclin D and acetylation of histone H3 and tubulin. Molecular docking analysis of the title compounds with the second deacetylase domain of HDAC6 displayed high degree of shape complementarity to the binding site of the enzyme, forming multiple molecular interactions in the hydrophobic region as well as a hydrogen bond to the phenol side-chain of Tyr-782. Thus, 1, 2, 3-triazole derivatives appear to represent a class of novel, biologically active ligands against histone deacetylases which deserve to be further evaluated in their applications in the cancer field.